Evaluating the genetic diversity in farmed populations of Nile tilapia (Oreochromis niloticus) from Brazil using SNP markers - Mastrochirico-Filho, Vito Antonio [UNESP]; Garcia, Baltasar Fernandes [UNESP]; Lira, Lieschen Valeria Guerra; do Amaral Neto, Antonio Ramon; Marín-Nahuelpi, Rodrigo; Gallardo-Hidalgo, Jousepth; Bassini, Liane Ney; Porto-Foresti, Fabio [UNESP]; Hashimoto, Diogo Teruo [UNESP] (Elsevier, 2025)
The Nile tilapia (Oreochromis niloticus) plays a significant role in global aquaculture, with Brazil ranking among the top producers worldwide. However, a considerable gap remains in the exploration of genetic diversity within Brazilian Nile tilapia stocks. To address this, we analyzed the genetic diversity of nine distinct farmed populations of Nile tilapia in Brazil, comprising a total of 600 individuals, using single-nucleotide polymorphisms (SNPs). Our objective was to provide essential genetic insights to establish the foundation for a new breeding nucleus. The pre-breeding populations exhibited high genetic diversity. Among them, Pop1 had the lowest diversity, characterized by the smallest proportion of polymorphic SNPs (NP = 92.3%), the lowest mean minor allele frequency (MAF = 0.24), and the lowest heterozygosity (HE = 0.32). In contrast, Pop5 and Pop9 displayed the highest genetic diversity (MAF = 0.30; HE = HO 0.39), with nearly all loci in Hardy-Weinberg equilibrium (HWE = 99.4%). Additionally, reduced effective population sizes (Ne) were observed in Pop1 (Ne = 6.8) and Pop4 (Ne = 15.4), with approximately 40 % of individuals classified as half-of full siblings, suggesting risks of inbreeding. These characteristics led to the genetic structuring of Pop1 and Pop4 in relation to the other populations, while Pop5 and Pop9 also formed a distinct cluster due to their higher genetic diversity. Despite the overall high genetic diversity observed across the analyzed populations, some populations exhibited parameters that may indicate potential future issues related to genetic diversity loss if not properly managed. Therefore, the findings presented here will help ensure the implementation of effective strategies during the pre-breeding phase of a new tilapia genetic improvement nucleus, supporting the long-term maintenance of genetic diversity in the breeding stock.